Implicit guarantees for bank debt where do we stand? - Schich, Sebastian (OECD Publishing, 2012)
The global financial crisis and the policy response to it have placed a sharp spotlight on the issue of implicit guarantees for bank debt. This report discusses the incidence of implicit government guarantees for bank debt, their determinants, and estimates of their value. It shows i) that the extent of implicit guarantees differs from one banking sector to another and, within a given banking sector, from one bank to another, ii) that implicit guarantees are higher the lower the bank's stand-alone creditworthiness, the higher the creditworthiness of its sovereign and the relatively bigger the bank in its domestic context, iii) that the incidence of implicit guarantees increased since the beginning of the financial crisis, but has decreased more recently, iv) that this recent decrease can be explained to a large extent by declining sovereign strength and hence a reduced capacity of on the part of many sovereigns to provide for such guarantees, but is also consistent with ongoing efforts in many OECD countries to make bank failure resolution regimes and practices more effective, and v) that implicit guarantees persist. Implicit guarantees imply an undesirably close link between the value of bank and sovereign debt. They also imply significant funding cost advantages for the banks that benefit from them, thus implying competitive distortions and an invitation to beneficiary banks to use them and, perhaps, take on too much risk
Keywords: Finance and Investment